Highly selective generation of singlet oxygen via peroxymonosulfate activation by Mn–N supported biochar - Huan Wu; Fangfang Ji; Bin Zhou; Shikun Gao; Zhe Zhang (AIP Advances)
In this study, manganese–nitrogen sites were incorporated into biochar (BC) to activate peroxymonosulfate (PMS) for the degradation of sulfamethoxazole (SMX). Characterization techniques, including scanning electron microscopy and others, confirmed the successful doping of Manganese–Nitrogen (Mn–N) sites into the BC (referred to as MnN@BC). The study revealed that the integration of Mn–N active sites in BC modified the electronic polarization and facilitated electron transfer. It is worth noting that a remarkable synergistic effect (SI = 6.92) was witnessed in the MnN@BC/PMS system. Under optimal conditions, SMX was nearly completely eliminated within 40 minutes. Radical scavenging experiments indicated that Hydroxyl Radical (•OH), Sulfate Radicals (SO4•−), superoxide radicals (O2•−), and singlet oxygen (1O2) all played significant roles in the degradation of SMX. Density functional theory calculations were employed to further investigate the mechanism of enhanced electron transfer of PMS facilitated by the loading of BC on the Mn–N site. Cyclic experiments and characterizations conducted before and after recycling demonstrated that MnN@BC exhibited remarkable stability and reusability. This study probed into the mechanism of PMS activation by transition metal and non-metal dual active sites and offered strategies for more effective and sustainable degradation of pollutants.